−6
6
8
Answer:
39⇒3
52⇒4
130⇒10
Step-by-step explanation:
hope this helps have a nice day!!!
B. (3x + 4)(x + 4)
C. (3x – 4)(x – 4)
D. (3x – 4)(x + 4)
Answer:
The factored form of the expression 3x + 8x – 16 is (3x -4) (x + 4) .
Option (D) is correct.
Step-by-step explanation:
As the expression given in the question be.
3x (x + 4) - 4 (x +4) = 0
(3x -4) (x + 4) = 0
Therefore the factored form of the expression 3x + 8x – 16 is (3x -4) (x + 4) .
Option (D) is correct.
Answer:
Refer the graph attached.
Step-by-step explanation:
Given : Equation
To find : The graph of the given equation?
Solution :
Let,
First we find the points which satisfy the equation and then joining those points give you the graph.
Points are
x y
-3 6
-2 3
-1 2
0 3
1 6
Now, We plot these points.
The graph is the parabola with vertex (-1,2).
Refer the attached graph below.
Answer:
first graph on edge
Step-by-step explanation:
A- a^0
B- 0
C- a^0 + 17
Let length be 12 ft (l = 12 ft) and width be 6 ft (w = 6ft).
The side pocket will be on the half of its length (l). To calculate the distance, we will use the distance d as a hypotenuse of the right triangle with sides w and l/2.
According to the Pythagorean theorem, the square of the hypotenuse is equal to the sum of the squares of two other sides:
d² = w² + (l/2)²
We have:
d = ?
w = 6 ft
l = 12 ft
d² = 6² + (12/2)²
d² = 6² + 6²
d²= 2 * 6²
d² = 2 * 36
d² = 72
d = √72
d = 8.48 ft
Since 1 ft is 12 in, then 8.48 ft is 101.76 in:
8.48 * 12 in = 101.76 in
Hope this helps!